Mathematical thinking in Brunei curriculum: implementation issues and challenges - Khalid, Madihah (2006)
Mathematical thinking has been identified as one of the important processes that should be developed through the teaching of mathematics content in the new Brunei mathematics curriculum. This new curriculum was introduced starting from early 2006. The emphasis on mathematical thinking in the new curriculum makes teachers in the elementary level anxious and eager to learn more about how it should be incorporated in their teaching. Many issues and challenges that arise as a result of these would be discussed in this paper. This paper will also look at how mathematical thinking is defined in the curriculum, discuss the key window for considering mathematical thinking and also discuss how mathematical thinking can be developed through lessons